Optimasi Pemilihan Lokasi Usaha Menggunakan Sistem Pendukung Keputusan Berbasis AHP - Bernadus Gunawan Sudarsono; Raditya Galih Whendasmoro (Bulletin of Information Technology (BIT), 2025)
In the midst of increasingly intense business competition and constantly changing market dynamics, the ability to make the right strategic decisions is crucial for an organization's success. Decision-making that involves various criteria often faces high complexity and subjectivity, requiring methods that can manage and simplify this process. Decision Support System (DSS) is a system designed to assist decision-makers in dealing with semi-structured or unstructured situations. This research aims to develop a decision support system based on the Analytic Hierarchy Process (AHP) that can help entrepreneurs determine the optimal business location. The Analytic Hierarchy Process (AHP) is a decision-making method developed by Thomas L. Saaty in the 1980s. A normalization matrix is used to determine the weight of each alternative. The aggregation of weights shows that alternative A3 has the highest rank, followed by alternative A2. Therefore, alternative A3 can be considered the best choice based on the predefined criteria. The AHP method helps in making more informed and objective strategic decisions by integrating various criteria and preferences, thus providing a comprehensive view in selecting the best alternative.